2016
DOI: 10.1038/leu.2016.214
|View full text |Cite
|
Sign up to set email alerts
|

The PD-1/PD-L1 axis contributes to immune metabolic dysfunctions of monocytes in chronic lymphocytic leukemia

Abstract: Immune dysfunctions in chronic lymphocytic leukemia (CLL) contribute to tumor immune escape and attenuate immune-based therapies. Monocytes/macrophages represent key components of cancer immune surveillance and effectors for antibody-mediated antitumor effects. Monocytes display an altered subset composition in CLL. Moreover, we find a changed metabolic phenotype: glucose uptake, glucose transporters and expression of glycolytic molecules are reduced. Our data establish a link between glycolytic competence and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
64
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(71 citation statements)
references
References 69 publications
0
64
0
3
Order By: Relevance
“…Therefore, it appeared that the types of CCR1 + cells were diverse in different tumor microenvironments. Mechanistically, aberrant expression of PD‐L1 was reported to reprogram monocytes toward the immune‐suppressive direction . In this study we showed that, in addition to immune checkpoint, upregulation of immune tolerogenic metabolic enzymes, inflammatory/pro‐antigenic cytokines and matrix remodeling proteases, as well as inflammatory chemokines, may collectively foster the pro‐tumor function of HCC‐infiltrating CCR1 + CD14 + monocytes.…”
Section: Discussionmentioning
confidence: 64%
“…Therefore, it appeared that the types of CCR1 + cells were diverse in different tumor microenvironments. Mechanistically, aberrant expression of PD‐L1 was reported to reprogram monocytes toward the immune‐suppressive direction . In this study we showed that, in addition to immune checkpoint, upregulation of immune tolerogenic metabolic enzymes, inflammatory/pro‐antigenic cytokines and matrix remodeling proteases, as well as inflammatory chemokines, may collectively foster the pro‐tumor function of HCC‐infiltrating CCR1 + CD14 + monocytes.…”
Section: Discussionmentioning
confidence: 64%
“…Metabolic communication among T cells, innate immune cells, and cancer might contribute to immunometabolic regulations and fine tuning of the activation and antitumor responses of T cells and myeloid cells (202) (Figure 4). In this regard, immunometabolic regulations mediated by coinhibitory receptors can impact T cell immune responses due to direct T cell-intrinsic signaling and by altering the metabolic properties and the differentiation program of innate immune cells (203). Not only the coinhibitory receptor ligands but also the coinhibitory receptors themselves are also present in various types of innate immune cells in addition to T cells.…”
Section: Coinhibitory Receptors Affect Immunometabolic T Cell Responsmentioning
confidence: 99%
“…Not only the coinhibitory receptor ligands but also the coinhibitory receptors themselves are also present in various types of innate immune cells in addition to T cells. Intriguingly, it was recently reported that the PD-1: PD-L1 axis is implicated in immune metabolic dysfunctions of monocytes in chronic lymphocytic leukemia (203). In that system, triggering PD-1 checkpoint on monocytes hampers glycolysis and phagocytosis.…”
Section: Coinhibitory Receptors Affect Immunometabolic T Cell Responsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, it has only recently been found that immune cells are also dependent on glycolysis to perform immune surveillance for cancer cells, and anything that restricts glycolysis may also impede immune actions against tumors. It is also reported that one function of current immune checkpoint inhibitors is to rescue immune cells from repressed glycolysis (Qorraj et al, 2016). …”
Section: Dietary Efforts To Aid Cancer Treatmentsmentioning
confidence: 99%